Application of CRISPR/Cas9 Genome Editing to Improve Recombinant Protein Production in CHO Cells - Grav, Lise Marie; Rojek, Johan Blatt; la Cour Karottki, Karen Julie; Lee, Jae Seong; Kildegaard, Helene Faustrup (Methods in Molecular Biology, 2025)
Genome editing has become an important aspect of Chinese hamster ovary (CHO) cell line engineering for improving the production of recombinant protein therapeutics. Currently, the engineering focus is directed toward expanding product diversity while controlling and improving product quality and yields. In this chapter, we present our protocol for using the genome editing tool Clustered Regularly Interspaced Short Palindromic Repeat (CRISPR)/CRISPR-associated protein 9 (Cas9) to knock out engineering target genes in CHO cells. As an example, we describe how to knock out the glutamine synthetase (GS) gene, which increases the selection efficiency of the GS-mediated gene amplification system.
Keywords: Animals; CHO Cells; Cricetulus; CRISPR-Cas Systems; Gene Editing; Gene Knockout Techniques; Glutamate-Ammonia Ligase; Recombinant Proteins; RNA, Guide, CRISPR-Cas Systems; Cas9; Chinese hamster ovary (CHO) cells; CRISPR; Genome editing; Glutamine synthetase; Knockout; Recombinant protein production